Characterization and improvement of curdlan produced by a high-yield mutant of Agrobacterium sp. ATCC 31749 based on whole-genome analysis. (1st October 2020) - Gao, Hongliang; Xie, Fangrui; Zhang, Wei; Tian, Jiangtao; Zou, Chunjing; Jia, Caifeng; Jin, Mingfei; Huang, Jing; Chang, Zhongyi; Yang, Xuexia; Jiang, Deming
Highlights: The curdlan biosynthesis mechanism can be determined based on whole-genome analysis. Mutant CGMCC 11546 produced 1.34-fold more curdlan than the WT strain. The maximum curdlan production was 47.97 ± 0.57 g/L (16 % increase) after optimization. Deletion of exoK and exsH increased the gel strength and molecular weight of curdlan. Noodles supplemented with curdlan from Δ exoK-exsH had excellent eating quality. Abstract: Curdlan is a bacterial, water-insoluble, linear homopolysaccharide that has been widely used in the food industry. In this study, genome information of strain CGMCC 11546, a UV-induced high-yield mutant of the model curdlan-producing strain Agrobacterium sp. ATCC 31749, was used to investigate the molecular mechanism of curdlan biosynthesis. The maximum curdlan yield of 47.97 ± 0.57 g/L was obtained from strain CGMCC 11546 by using optimal media containing 60 g/L sucrose, 6 g/L yeast, 2 g/L KH2 PO4, 0.4 g/L MgSO4 ·7H2 O, 2 g/L CaCO3, 0.1 g/L FeSO4 ·7H2 O, 0.04 g/L MnSO4, and 0.02 g/L ZnCl2 at 30 °C and 280 rpm after 96 h of fermentation. The gel strength of curdlan was improved by 41 % by knocking out the β-1, 3-glucanase genes exoK and exsH of strain CGMCC 11546. Furthermore, the application of curdlan from the Δ exoK-exsH strain in noodles significantly improved the eating quality of both raw and cooked noodles.